Implications of Single Motherhood on Primary Education in Anambra State, Nigeria - Umeji, Ifeoma Chinyere (Lembaga Riset Mutiara Akbar, 2024)
Single motherhood can impact primary education by limiting children’s academic support and increasing emotional challenges, potentially leading to behavioral issues and lower academic performance. This study investigated the implications of single motherhood on primary education in Anambra State, Nigeria. Employing a descriptive survey research design, the study targeted primary school teachers across Anambra State as key informants due to their role in observing and supporting students’ development. Using a simple random sampling method, 400 teachers were selected, and data were collected through a structured questionnaire. The questionnaire's validity was confirmed through expert review, and a pilot test yielded a reliability score of 0.71. Data were analyzed using mean and standard deviation to identify trends and patterns. Findings revealed that children from single-mother households often experience reduced parental guidance, emotional challenges, and behavioral issues that impact their academic and social development. However, strong mother-child bonds and community support services were identified as positive influences that can mitigate some of these challenges. The study underscores the importance of tailored support for single-parent households, emphasizing self-care strategies, community resources, and open parent-child communication. The findings suggest that educational stakeholders and policymakers should prioritize resources and programs that address the unique needs of children in single-mother families, fostering a more inclusive educational environment.